STRATEGI MANAJEMEN MUTU DALAM MEMBANGUN HUBUNGAN SALING MENGUNTUNGKAN ANTARA SEKOLAH DAN KANTIN SEKOLAH - Shofiyyah, Alya; Gede Dian Puspita, Ni Luh; Weki Sera, Salvator Ronaldo; Azainil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify quality strategies in building mutually beneficial relationships between schools and school canteens. The research method used is a case study with qualitative analysis. The results of the study indicate that effective quality strategies in building mutually beneficial relationships between schools and school canteens include: Effective communication: Schools and school canteens must have effective communication to understand each other's needs and expectations. Good cooperation: Schools and school canteens must have good cooperation to achieve common goals. Quality control: Schools must supervise the quality of food and drinks sold in school canteens. Healthy menu development: School canteens must provide healthy and nutritious menus for students.